2019
DOI: 10.1088/1742-6596/1351/1/012111
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Environment Feel in Learning through the Double S Application

Abstract: In this era of globalization, English has become the second language for some non-English speaking countries. But in Indonesia, English is actually being a foreign language. This is because learning English in junior high school is monotonous and boring. So students’ interest in learning is reduced. The purpose of this study is to create a media for learning English so that it can increase interest the environment feel in learning and trigger students’ enthusiasm in learning English subjects. The learning medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Quoted from the website of the world's largest ranking of English skills, students' English skills in Indonesia are still low. In 2018, Indonesia ranked 51 out of 88 countries worldwide (Islami, 2019). It is also strengthened by Purwani & Dewi (2021) confirmed that learning English at the university level is one of the general compulsory subjects.…”
Section: Introductionmentioning
confidence: 96%
“…Quoted from the website of the world's largest ranking of English skills, students' English skills in Indonesia are still low. In 2018, Indonesia ranked 51 out of 88 countries worldwide (Islami, 2019). It is also strengthened by Purwani & Dewi (2021) confirmed that learning English at the university level is one of the general compulsory subjects.…”
Section: Introductionmentioning
confidence: 96%